New Zealand : 2017 Article IV Consultation- Press Release; Staff Report; and Statement by the Executive Director for New Zealand. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights New Zealand's economic expansion, which since early 2011 gained further broad-based momentum in 2016. GDP growth accelerated to 4 percent, and the output gap has roughly closed. Reconstruction spending after the 2011 Canterbury earthquake was an important catalyst, but the expansion has also been supported by accommodative monetary policy, a net migration wave, improving services exports, and strong terms of trade. There was some weakening of momentum in the fourth quarter of 2016, owing to softer private consumption and a sharp drop in exports, but it is expected to be temporary. Growth should rebound and then moderate toward trend in the medium term, in particular as net migration normalizes.